2013
DOI: 10.1089/scd.2012.0461
|View full text |Cite
|
Sign up to set email alerts
|

A Hierarchy in Reprogramming Capacity in Different Tissue Microenvironments: What We Know and What We Need to Know

Abstract: Ectopic expression of certain transcription factors induces reprogramming of somatic cells to a pluripotent state. A number of studies have shed light on the reprogramming capacity of various cell populations. As a result, it has been shown that stem/progenitor cells derived from organs of all germ layers exhibit a superior reprogramming efficiency compared to their differentiated progeny. Although proliferative capacity and endogenous expression levels of pluripotency factors are likely to be involved in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 82 publications
0
26
0
Order By: Relevance
“…A number of studies have revealed that immature cells (stem/progenitors) exhibit a superior reprogramming efficiency as compared to their differentiated progeny [12,13,25,26]. Our data indicates that throughout B-cell development, cellular hierarchy also influences reprogramming efficiency into iPSCs.…”
Section: Resultsmentioning
confidence: 63%
“…A number of studies have revealed that immature cells (stem/progenitors) exhibit a superior reprogramming efficiency as compared to their differentiated progeny [12,13,25,26]. Our data indicates that throughout B-cell development, cellular hierarchy also influences reprogramming efficiency into iPSCs.…”
Section: Resultsmentioning
confidence: 63%
“…Nevertheless, some disadvantages of reprogramming fibroblasts such as their relatively low reprogramming efficiency and especially the need of uncomfortable biopsies have led to a search for other cell sources. The molecular properties of the different cell types leading to variations in the reprogramming efficiency have been reviewed in [14]. Publications describe, amongst others, three relatively easy to obtain cell types, that is, blood cells [15], exfoliated renal tubular epithelial cells, obtained from urine [16], and keratinocytes from plucked hair [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, understanding early fate decision events, such as segregation of the three germ layers, is a prerequisite for regenerative medicine [15]. The advent of induced pluripotent stem cells and their unique features of unlimited self-renewal and nonrestricted differentiation capacity marked a milestone in the battle to dissect such processes—directly in the context of human development [68]. Given the incredible accordance of embryonic development in vivo and its respective model system in vitro , it is not surprising that most of the currently available pluripotent stem cell differentiation protocols make use of physiological, stage-specific signalling clues in order to recapitulate development of all three germ layers: ectoderm, mesoderm, and endoderm.…”
Section: Introductionmentioning
confidence: 99%